Membangun Kompetensi Paralegal Dalam Hukum Agraria Dan Sengketa Lahan Di Desa Deme Dua Kec. Sumalata Timur - Daud Rahim; Rustam Akili; Yusrianto Kadir; Nurwita Ismail (AMMA : Jurnal Pengabdian Masyarakat, 2025)
With effective land dispute resolution, agricultural productivity and the welfare of village communities can increase. Non-disputed land can be optimally utilized for economic activities that benefit the community. The method of implementing this service activity is in several stages: coordination with the village community, literature study, and face-to-face socialization. The results of community service on paralegal training where the presence of deme dua village paralegals can help minimize the occurrence of land cases in the village, existing cases can be handled more effectively and efficiently. The presence of village paralegals is one of the alternatives to researching local village conflicts. It can also help in resolving disputes peacefully and effectively before the problem becomes bigger. The settlement of land disputes that have not been certified is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 21 of 2020 concerning the Handling and Settlement of Land Cases. Paralegals act as mediators, the duties of mediators are based on article 14 of Perma no. 1 of 2016 concerning mediation procedures.